WOMEN AGAINST GENDER INEQUALITY IN HARRY BREADBEER’S MOVIE ENOLA HOLMES 2 - Pardede, Tama Riska; Hartati, Rita (Universitas Negeri Medan, 2023)
This paper aims to analyze the types of gender inequality that occur in the Enola Holmesmovie and describe the woman's struggle against gender inequality by referring to Walby's(1991) and Lakoff’s (2013) theories to explain the representation of women language usedby female characters in the Enola Holmes 2 movie. This study uses a descriptive qualitativeresearch method with data obtained from the film Enola Holmes 2. The result of this studyindicate that there are 24 utterances featuring gender inequality categories by femalecharacters. The findings are that there are five gender inequality categories, namelyviolence and culture (33,33%), the state, household production (12,5%) and paid work(8,34%). The reasons why women struggle against the five categories of gender inequalityare because they want gender equality in all scopes, especially the scope of work, to beequal for everyone. The dominant types of women's language used in the Enola Holmes 2movie are rising intonation on declarative, intensifiers, and emphatic stress to emphasizethe utterance's meaning, and super-polite forms to show respect and politeness and revealthe social class of the women.Keywords: Gender Inequality, Woman Language, Enola Holmes Movie